Influence of religiosity and customs law towards import duty noncompliance behavior in Malaysia - Yusoff, Yusri Hazrol; Yusri, Yusniyati; Ong, Tze San; Selamat, Aslam Izah (South East Asia Journal of Contemporary Business, Economics and Law, 2018)
The issue on tax noncompliance has been critically discussed by the government and academic researchers due to its indirect impact on the country’s social and economic development. The present study was undertaken to examine the Malaysian taxpayer’s noncompliance behaviour, with the intention of adapting the Theory of Planned Behaviour (TPB) to describe the behaviour and actions taken by the noncompliant taxpayers. A total of 117 taxpayers from noncompliant companies in the year 2015 were sampled and analyzed. The findings revealed strong positive effects of Religiosity and Customs Law on import duty noncompliance behavior when the relationship was supported by the element of intention not to comply.In using a revised TBP framework, the study makes a significant theoretical contribution to the literature on indirect tax. Furthermore, this study has a number of practical implication for the Royal Malaysia Customs Department as the authority agency in terms of combating noncompliance issue.